Sie sind auf Seite 1von 1

Integrales Inmediatas

x n +1 1
∫x
n
dx =
n +1
+c  n = −1  ∫ x dx = ln x + c

n=0  ∫ dx = x + c

ax
∫ a dx =
x
+c  a=e  ∫e
x
dx = e x + c
ln a

∫ Senxdx = −Cosx + c ∫ Senhxdx = Coshx + c


∫ Cosxdx = Senx + c ∫ Coshxdx = Senhx + c
∫ Tgxdx = − ln Cosx + c = ln Secx + c ∫ Tghxdx = ln Coshx + c
∫ Ctgxdx = ln Senx + c ∫ Ctghxdx = ln Senhx + c
∫ Secxdx = ln( Secx + Tgx ) + c ∫ Sechxdx = ArcTgSenhx + c
∫ Cscxdx = ln( Cscx − Ctgx ) + c ∫ Cschxdx = − ArgThCoshx + c
∫ Sec xdx = Tgx + c ∫ Sech xdx = Tghx + c
2 2

∫ Csc xdx = −Ctgx + c ∫ Csch xdx = −Ctghx + c


2 2

∫ SecxTgxdx = Secx + c ∫ SechxTghxdx = − Sechx + c


∫ CscxCtgxdx = −Cscx + c ∫ CschxCtghxdx = −Cschx + c


1
x +1
2
(
dx = ArgSenhx + c = ln x + x 2 + 1 + c )
1
∫ dx = ArcSenx + c 1
dx = ArgCoshx + c = ln ( x + − 1) + c
1− x2 ∫ x2
−1
x2
1
∫ 1 + x 2 dx = ArcTgx + c 1 1 1+ x 
1
∫ 1 − x 2 dx = ArgTghx + c = 2 ln 1 − x  + c
∫ x x 2 − 1 dx = ArcSecx + c  1+ 1− x2 
1  +c
∫ x 1− x2 dx = − ArgSechx + c = − ln
 x 
 